EFFECT OF ANTIBIOTICS TREATMENT ON HUMORAL IMMUNITY IN SHEEP VACCINATED WITH B. melitensis REV.1 VACCINE - Aldabagh, I.; Mohammad, M.; Ali, M . (Iraqi Journal of Science, 2024)
The aim of this study was to examine the effects of different antibiotics administered intramuscularly with a different administration times on the humoral immune response resulted from intraocular vaccination with attenuated B. melitensis Rev.1 vaccine in sheep. The results showed a significant difference in the effect of different antibiotics used with a significant difference according to the administration time between 0 time, 7 and 14 days from vaccination. Oxytetracycline and amoxicillin significantly inhibit the humoral immune response when administrated at 0, 7 and 14 days of Brucella vaccination comparing with groups treated with sulphadimidine, penicillin-dihydrostreptomycin and the non-vaccinated groups while sulphamethazine – trimethoprim inhibit the humoral immune response when administrated at 0 time of vaccination comparing with groups treated with sulphadimidine, penicillin-dihydrostreptomycin and the non-vaccinated groups. The results indicate that the failure of Brucella vaccination could happen when antibiotics administered within the first 14 days after vaccination.